2008
DOI: 10.1080/00268970802665605
|View full text |Cite
|
Sign up to set email alerts
|

Directab initiomolecular dynamics study of F atom reaction with methane

Abstract: The dynamics of the F þ CH 4 ! HF þ CH 3 and F þ CD 4 ! DF þ CD 3 reactions have been investigated using classical trajectory calculations at the MP2/cc-pvdz level of theory. The trajectories were calculated directly from electronic structure computations, and a Hessian based method with updating was used to integrate the trajectories. Using this method, product rovibrational populations and internal energy distributions were obtained for the F þ CH 4 and F þ CD 4 reactions. The theoretical results were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These notions are confirmed by ab initio calculations. 4,5,[50][51][52][53][54][55] One of the theoretical studies further indicated two low intermolecular bending frequencies (40 cm À1 and 117 cm À1 ) at the reaction saddle point, 4,5 implying a loose-bend transition state. In addition, two van der Waals (vdW) complexes of C 3v symmetry are calculated in the reactant channel.…”
Section: Stereodynamical Implicationsmentioning
confidence: 99%
“…These notions are confirmed by ab initio calculations. 4,5,[50][51][52][53][54][55] One of the theoretical studies further indicated two low intermolecular bending frequencies (40 cm À1 and 117 cm À1 ) at the reaction saddle point, 4,5 implying a loose-bend transition state. In addition, two van der Waals (vdW) complexes of C 3v symmetry are calculated in the reactant channel.…”
Section: Stereodynamical Implicationsmentioning
confidence: 99%
“…A typical example is the investigation of the reaction between fluorine atoms and different isotopologues of methane. The last 15 years have witnessed the realization of detailed experiments on such systems, which uncovered several interesting dynamical features. However, among those experimental results, only the photodetachment spectra of FCH 4 – and FCD 4 – (refs and ) could be contrasted against rigorous first-principle-based computations. In other cases, quasiclassical trajectories (QCT) or reduced dimensionality calculations were employed to reproduce and interpret the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported an experimental investigation on the effects of reactant’s bending excitations in the F + CD 4 → DF + CD 3 reaction . The reaction of F + CD 4 is highly exothermic (Δ H rx = −31.13 kcal mol –1 ) and very fast ( k = 6.7 × 10 –11 cm 3 molecule –1 s –1 at 298 K) , with an early barrier. To scrutinize the bend-excited reactivity, the experiment was performed under the crossed-beam conditions, using a time-sliced velocity-imaging technique to probe the predominant ground-state methyl radical products, CD 3 (0 0 ,low N -states) . Two major findings were reported.…”
Section: Introductionmentioning
confidence: 99%